2005
DOI: 10.1111/j.1523-1755.2005.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin stimulates proinflammatory and proliferative responses in primary cultures of human proximal tubule cells

Abstract: Thrombin initiates both proinflammatory and fibroproliferative responses in human PTC. These responses which are dependent on its protease activity appear not to be mediated by PAR-1 activation, the autocrine action of thrombin-induced TGF-beta1 secretion, MMP activation, or EGF receptor transactivation. The proinflammatory and fibroproliferative actions of thrombin on human PTC may help explain the extent of tubulointerstitial fibrosis observed in kidney diseases where fibrin deposition is evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 67 publications
1
52
2
Order By: Relevance
“…Several models of PAR trans-and coactivation have been proposed (11,(21)(22)(23)(24)(25). Studies showed that platelet-specific PAR1/4 heterodimerization was responsible for thrombininduced platelet aggregation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Several models of PAR trans-and coactivation have been proposed (11,(21)(22)(23)(24)(25). Studies showed that platelet-specific PAR1/4 heterodimerization was responsible for thrombininduced platelet aggregation (26).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the conditioned media were concentrated 20-fold with Nanosep 3K omega spin columns (Pall Life Sciences, Melbourne, Australia) before use. Cells were washed twice with ice-cold PBS, incubated at 4°C for 10 min with lysis buffer, and prepared for electrophoresis as previously described (34). Equal amounts of conditioned medium or cell protein were diluted in a reducing SDS-PAGE sample buffer, heated to 70°C for 10 min, separated on a 4 -12% NuPAGE gel (Invitrogen, Mt Waverley, Australia) and electrotransferred to a polyvinylidene difluoride membrane (Pall Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…The method for isolation, culture, and characterization of PTC is described in detail elsewhere (7,18,34). Briefly, the cortical tissue was minced finely, washed several times, and agitated for 20 min at 37°C in Krebs-Henseleit buffer (KHB) containing collagenase type II (1 mg/ml), (Worthington, Freehold, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations